2022
DOI: 10.1021/acschemneuro.2c00512
|View full text |Cite
|
Sign up to set email alerts
|

Could Amyloid-β 1–42 or α-Synuclein Interact Directly with Mitochondrial DNA? A Hypothesis

Abstract: The amyloid β (Aβ) and the α-synuclein (α-syn) are shown to be translocated into mitochondria. Even though their roles are widely investigated in pathological conditions, information on the presence and functions of Aβ and α-syn in mitochondria in endogenous levels is somewhat limited. We hypothesized that endogenous Aβ fragments or α-syn could interact with mitochondrial DNA (mtDNA) directly or influence RNAs or transcription factors in mitochondria and change the mtDNA transcription profile. In this review, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 122 publications
1
1
0
Order By: Relevance
“…The interaction of αSyn with mitochondria may occur not only through mitochondrial deoxyribonucleic acid, as previously predicted, but also through mitochondrial chaperones GRP75 is a mitochondria-associated membrane chaperone essential for regulating mitochondrial turnover and involved in energy production processes, , we did not find any significant change at the intracellular level of this chaperone. Conversely, another mitochondrial chaperone, Hsp10, displayed an increase in levels within the first 12 h in the control group, a response not observed in the presence of fibrils.…”
Section: Discussionsupporting
confidence: 82%
“…The interaction of αSyn with mitochondria may occur not only through mitochondrial deoxyribonucleic acid, as previously predicted, but also through mitochondrial chaperones GRP75 is a mitochondria-associated membrane chaperone essential for regulating mitochondrial turnover and involved in energy production processes, , we did not find any significant change at the intracellular level of this chaperone. Conversely, another mitochondrial chaperone, Hsp10, displayed an increase in levels within the first 12 h in the control group, a response not observed in the presence of fibrils.…”
Section: Discussionsupporting
confidence: 82%
“…For example, does α-synuclein interact with mitochondrial DNA directly and influence transcription profile? What role synucleins play in endoplasmic reticulum-Golgi traffic [ 89 ]? Recent studies investigating microtubule dynamics showed that α-synuclein facilitated the formation of short microtubules and favorably binds to 4 protofilaments.…”
Section: Discussionmentioning
confidence: 99%